Priority Scheduling and Spares Stocking Policies for a Repair Shop: The Multiple Failure Case - Scudder, Gary D. (Management Science, 1984)
Improved scheduling rules and spares stocking policies are examined for a repair shop supporting a multi-item repairable inventory system with a hierarchical product structure. The results from an earlier paper are extended to the case where more than one unit fails in each item to be repaired. A variety of scheduling rules and methods for initializing the vector of spare parts are evaluated using a simulation of a representative shop. The results indicate that procedures which perform well when only a single unit fails also perform well when multiple failures occur. More complex rules, which recognize assembly mating requirements, do not appear to provide any significant improvement.